Desarrollo de electrodo basado en cobre-quitosano-cobre como sensor electroquímico para medición de dqo en aguas residuales. - Carrion Obaco, Jessica Gabriela (2017)
Pollution of water resources is a global problem connotation; in the same way, the quantification methods pollution characteristics are varied among the most representative are those that measure the amount of organic matter present in water. One of the most important is the so-called COD Chemical Oxygen Demand.The development of electroanalytical techniques aims to reduce reagent costs, timing analysis, use of harmful reagents for human and environmental health, between what can be achieved with the application of electrodes Cu, thereof which are easy to prepare and modification , while exhibiting good relative stability. An alternative for the measurement of COD, is the preparation of modified Cu electrodes chitosan film as electrochemical sensor and an electrochemical treatment with Cu nanoparticles that electrodeposited on the surface thereof. Likewise, it is no less important validation analysis methodologies, parameters such as detection limit, accuracy, sensitivity, linearity, accuracy, repeatability, reproducibility, the same that are fundamental electrochemical techniques. The objective of this research is based on Cu electrode modified with chitosan and copper nanoparticles as an electrochemical sensor for COD measurement, the same was carried out using the computer Potentiostat CH Intruments series 1220B, driven by a CHI software 1220b .the behavior of electrochemical oxidation of organic compounds in samples of actual water was studied using the electrochemical method, the experimental conditions evaluated were: speed exploration potential number of cycles, concentration of electrolyte and parameters of analytical validation . The potential change in the negative, the oxidation peak current greatly increases in the NCU surface, resulting in a simple, accurate, rapid and sensitive electroanalytical method.Nanoparticles Cu in Cu / CHI were electrodeposited in 10 ml solution of CuSO4 / H2SO4 with cyclic voltammetry technique capable voltage potential -1.3 V -0.1 and scan rate of 100 mV / s.Additionally prepared standard glucose solutions of 10 mM, 8 mM, 6 mM, 4 mM, 2 mM concentrations and white with ELECTROLYTE NaOH 0.1 M.